2011
DOI: 10.2341/11-029-l
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Cuspal Coverage of Endodontically Treated Maxillary Premolars with Combined Composite-Amalgam Compared to Other Techniques

Abstract: Combined composite-amalgam for cuspal coverage of endodontically treated premolars was similar to direct composite coverage in strengthening restored teeth; however, composite onlay had the highest fracture resistance. SUMMARYThis in vitro study investigated the fracture resistance of teeth restored with combined composite-amalgam for cuspal coverage compared to direct coverage with composite (with or without an amalgam base) and composite onlay. Seventy-two intact maxillary premolars were randomly divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…The values were markedly lower in MODP and MODPB models, regardles of the use of a FRC post. These findings are in accordance with the results of certain studies 8,13,23,24) . In a FEA study, Lin et al 13) recommend a cusp reduction of at least 1.5 mm in order to increase the fracture resistance of premolars.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The values were markedly lower in MODP and MODPB models, regardles of the use of a FRC post. These findings are in accordance with the results of certain studies 8,13,23,24) . In a FEA study, Lin et al 13) recommend a cusp reduction of at least 1.5 mm in order to increase the fracture resistance of premolars.…”
Section: Discussionsupporting
confidence: 93%
“…Kantardžić et al 23) found using the FEA method that the reduction of the palatal cusp reduces stresses in the enamel significantly. Certain in vitro studies showed that endodontically treated premolars restored using partial ceramic 24) or full composite onlays 8) had a higher fracture resistance as compared to other techniques used, while another group of authors 6) found that cusp capping does not influence fracture resistance significantly. In the present study MODP and MODP+P showed the lowest values of maximum von Mises stresses in the enamel, which could indicate that bucal premolar cusp reduction is not necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compressive loading during the fracture resistance test may be distributed throughout the restored tooth by different materials. Thus, Shafiei et al (2014) [80] suggested covering the cusps with an amalgam and composite resin combination and found no difference between the group receiving direct composite coverage and the one undergoing amalgam-based composite restoration. Nevertheless, direct cusp coverage with composite restoration appears to be a reliable method in extensive cavities [44,73].…”
Section: Fiber-reinforced Composite Materialsmentioning
confidence: 99%